Camellia oil authentication: A comparative analysis and recent analytical techniques developed for its assessment. A review - Shi, Ting; Wu, Gangcheng; Jin, Qingzhe; Wang, Xingguo (Trends in food science & technology, 2020)
Camellia oil is obtained from the camellia seed with various cultivated species (Camellia. oleifera (C. oleifera), C. meiocarpa, C. vietnamensis, C. yuhsienensis, C. chekiangoleosa, C. semiserrata, C. reticulata, C. gigantocarpa, C. octopetala, C. semiserrata var. abliflora etc.), by widely used cold press extraction. As the earliest specie with high oil yield (40–60%) in China, C. oleifera, has become the most commonly available seed for camellia oil manufacturing. Because of its high nutritional and economic value, camellia oil is frequently adulterated with other cheap oils. Additionally, its quality is also susceptible to different species or regions, and various extraction technologies. These factors result in the incorrect labeling of camellia oil, and destabilize the local camellia oil market economies. Therefore, a rapid and accurate method should be prerequisite to authenticate camellia oil. The officially recommended methods are tedious, and destructive to detect camellia oil adulteration. Therefore, various rapid, precise, and non-destructive techniques should be developed for camellia oil authentication. This present review provides a critical overview of these existing analytical methods in the past few years. The mass-chromatographic, spectroscopy techniques, and other techniques including electronic noses (e-noses), isotope-ratio mass spectrometry (IRMS), differential scanning calorimetry (DSC), ion mobility spectrometry (IMS) and DNA, have been used for camellia oil authentication. Compared with the traditional chromatographic methods, infrared spectroscopy (IR), Fourier transformed (FT)-Raman, nuclear magnetic resonance (NMR), and fluorescence spectroscopy, combined with chemometrics, respectively, are efficient alternative analytical techniques for camellia oil quality control. •Camellia oil is frequently adulterated with other cheap oils.•Camellia oil quality is susceptible to different species and extraction methods.•Various rapid and non-destructive techniques could authenticate camellia oil.•Spectroscopy with chemometrics is efficient for camellia oil authentication.